The Concept Of The State From The Fiqh Siyasah Perspective - Alexander, Ongky; Fauzi, Muhamad; Kuswoyo, Bahed Edi; Yani, Ahmad; Nasri, Halik; Siswoyo, Siswoyo (El-Ghiroh : Jurnal Studi Keislaman, 2025)
The siyasa approach in understanding the concept of the state offers a comprehensive paradigm, with spiritual and moral dimensions as the main foundation. In this perspective, the state is not just a political entity, but a divine mandate that must be carried out to realize noble goals: upholding justice ('adl) and safeguarding the benefit of the people (maslahah). This article explores the essence, functions and characteristics of an ideal state according to siyasah fiqh, which includes implementing sharia fairly, protecting individual and collective rights, strengthening social justice, and realizing the unity of the people in diversity. By exploring the thoughts of classical scholars such as Al-Mawardi and Ibn Khaldun, this article not only offers historical reflections, but also examines the relevance of the concept of siyasa in facing modern challenges. The dynamics of globalization, secularization and the hegemony of the Western political system are major tests in the application of siyasa values. This research uses a literature study methodology as the main method. For data collection methods from various literature, this study also involves comparative analysis between traditional theories and modern political reality. The conclusion of this study confirms that although the modern world presents new complexities, spiritual and moral values ??in siyasah remain relevant. Therefore, creative and innovative strategies are needed to transform these values ??so that they can be applied effectively in today's global context.